Process for making a wear resistant high pore volume silica-alumina material

CN123022497APending Publication Date: 2026-10-30RELIANCE IND LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580024434.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-02-03
Filing Date
2025-02-01
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

由于钠的存在以及有机二氧化硅源和氧化铝源的高成本,其合成变得复杂

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present disclosure relates to a method for preparing a wear resistant high pore volume silica-alumina material. The wear resistant high pore volume silica-alumina material is obtained by hydrothermal treatment of a silica and alumina gel or sol. The method is simple, efficient, cost effective and provides a high pore volume silica-alumina precursor as well as a wear resistant high pore volume silica-alumina material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a method for preparing wear-resistant, high-porosity silica-alumina materials.

[0002] definition

[0003] Unless the context otherwise requires, the following terms are generally intended to have the meanings described below.

[0004] Wear Index: The term "wear index" refers to the amount of fine powder formed from silica-alumina materials / catalysts due to physical wear, abrasion, and / or grinding of particles during use in catalytic conversion processes or test units. A lower wear index (< 10) indicates that the material has high wear resistance. The wear index of the catalyst / material is measured using the ASTM D5757 / Jet cup method.

[0005] Sol: The term "sol" refers to the liquid state of a colloidal solution.

[0006] Gel: The term "gel" refers to a solid or semi-solid colloidal solution. Background Technology

[0007] The background information below is relevant to this disclosure, but is not necessarily prior art.

[0008] Silica-alumina (SAM) materials are used as supports and catalysts in the refining and chemical industries. The ideal high pore volume, large surface area, and pore size are key characteristics of SAM materials. Furthermore, SAMs are relatively stable materials with tunable shape and porosity. While their Brønsted acid sites and catalytic activity are undoubtedly lower than zeolites, their lower tendency to coke makes them more preferred in certain applications. Moreover, these materials exhibit tunable properties for metal and cation centers, making them extremely important and versatile catalyst supports. Due to their surface acid sites and localized structure, silica-alumina materials with large pore volumes have found applications in industrially significant methods. High-pore-volume materials can accommodate higher concentrations of active metal components, which promotes their application in coal and biomass catalytic gasification.

[0009] In known methods, sodium-containing silica sources are used to manufacture high-porosity silica-alumina materials. These methods utilize expensive organoaluminum and silica sources as their metal alkoxides. The synthesis is complicated by the presence of sodium and the high cost of both organoaluminum and alumina sources. Furthermore, removing the salts present in the silica-alumina mixture is a challenging process.

[0010] The wear index, particle size, and bulk density of silica-alumina materials are important characteristics for their application in fluidized bed catalytic processes for coal and biomass gasification. Therefore, the preparation of silica-alumina materials with the aforementioned properties for various industrial catalytic applications is desirable.

[0011] Therefore, there is a need to provide a method for preparing wear-resistant, high-porosity silica-alumina materials to mitigate the above-mentioned disadvantages or at least provide an alternative.

[0012] Purpose of the invention

[0013] Some of the objectives of this disclosure (at least one embodiment herein satisfies these objectives) are as follows: One object of this disclosure is to improve one or more problems in the prior art, or at least to provide a useful alternative.

[0014] Another object of this disclosure is to provide a method for preparing wear-resistant, high-porosity silica-alumina materials.

[0015] Another objective of this disclosure is to provide a high-pore-volume silica-alumina precursor by hydrothermal treatment of silica and alumina gels or sols using sodium-free silica and alumina sources.

[0016] Another object of this disclosure is to provide a simple, sustainable and economical method for preparing wear-resistant, high-porosity silica-alumina materials.

[0017] Other objects and advantages of this disclosure will become more apparent from the following description, which is not intended to limit the scope of this disclosure. Invention Overview

[0019] This disclosure relates to a method for preparing wear-resistant, high-porosity silica-alumina material. In embodiments of this disclosure, the method for preparing the wear-resistant, high-porosity silica-alumina material includes preparing a high-porosity silica-alumina precursor by acidifying colloidal silica particles with an acid to obtain acidified silica with a predetermined pH value. An aluminum precursor solution is prepared separately by dissolving the aluminum precursor in water with stirring at a temperature in the range of 20°C to 40°C. The obtained aluminum precursor solution is added to the acidified silica with stirring to obtain a silica-alumina sol. At least one alkali is added to the silica-alumina sol to bring the pH value to the range of 7 to 8 to obtain a gel. The obtained gel is hydrothermally heated in an autoclave at a first predetermined temperature for a first predetermined time period to obtain a heated gel. The heated gel is cooled to a temperature in the range of 25°C to 40°C, then filtered to obtain a solid, and the solid is washed with an ammonia solution with a pH value in the range of 7 to 9 to obtain a wet filter cake of the high-porosity silica-alumina precursor. Optionally, the wet filter cake is dried at a second predetermined temperature for a second predetermined time period, followed by calcination at a third predetermined temperature for a third predetermined time period to obtain a high-porosity silica-alumina precursor. Alternatively, the wet filter cake or high-porosity silica-alumina precursor is mixed with at least one binder, at least one stabilizer, and water at a temperature ranging from 25°C to 40°C to obtain a slurry. The slurry is spray-dried at a fourth predetermined temperature for a fourth predetermined time period to obtain a spray-dried material in the form of microspheres. The obtained spray-dried material is calcined at a fifth predetermined temperature at a predetermined heating rate for a fifth predetermined time period to obtain a wear-resistant high-porosity silica-alumina material.

[0020] According to embodiments of this disclosure, the acid is at least one selected from nitric acid, sulfuric acid, formic acid, and acetic acid.

[0021] According to the embodiments of this disclosure, the acid is a concentrated acid with a concentration of 65% or higher.

[0022] According to embodiments of this disclosure, the predetermined pH value of the acidified silica is in the range of 2.5 to 4.

[0023] According to embodiments of this disclosure, colloidal silica is preferably sodium-free silica. According to one embodiment of this disclosure, the particle size of the colloidal silica is in the range of 10 nm to 20 nm.

[0024] According to embodiments of this disclosure, the aluminum precursor is selected from at least one of aluminum nitrate, aluminum sulfate, aluminum acetate, aluminum formate, aluminum chloride, aluminum oxide, aluminum hydroxide, and aluminum trihydride.

[0025] According to embodiments of this disclosure, a nonionic surfactant is added to the gel prior to hydrothermal heating. The nonionic surfactant is a block copolymer of polyethylene glycol and polypropylene glycol (Pluronic P123).

[0026] According to embodiments of this disclosure, the alkali is selected from aqueous ammonia solution and organic amines.

[0027] According to the embodiments of this disclosure, the first predetermined temperature is in the range of 150°C to 200°C.

[0028] According to the implementation scheme of this disclosure, the first predetermined time period is within the range of 20 to 30 hours.

[0029] According to the embodiments of this disclosure, the second predetermined temperature is in the range of 100°C to 150°C.

[0030] According to the implementation scheme of this disclosure, the second predetermined time period is in the range of 6 hours to 24 hours.

[0031] According to the embodiments of this disclosure, the third predetermined temperature is in the range of 500°C to 700°C.

[0032] According to the implementation scheme of this disclosure, the third predetermined time period is in the range of 1 to 5 hours.

[0033] According to embodiments of this disclosure, the adhesive is selected from reactive colloidal silica and pseudoboehmite alumina.

[0034] According to embodiments of this disclosure, the stabilizer is selected from urea, ammonium carbonate, ammonium bicarbonate, sodium hexametaphosphate, polycarboxylic acid ether, citric acid, oxalic acid, ammonium salts of polyacrylic acid, polydiallyldimethylammonium chloride, hexamethylenetetramine (HMTA), ethylenediaminetetraacetic acid (EDTA), polyacrylamide, and derivatives thereof.

[0035] According to embodiments of this disclosure, the surfactant is selected from octylphenol ethylene oxide condensate, hexadecyltrimethylammonium bromide, a block copolymer of polyethylene glycol and polypropylene glycol (Pluronic P123 block copolymer), and octylphenol ethoxylate.

[0036] According to the embodiments of this disclosure, the solid content of the slurry is in the range of 10% to 30% by mass, and the moisture content of the slurry is in the range of 70% to 90% by mass.

[0037] According to the embodiments of this disclosure, the fourth predetermined temperature is in the range of 150°C to 450°C; and the fourth predetermined time period is in the range of 15 minutes to 60 minutes.

[0038] According to embodiments of this disclosure, spray drying is performed using a spray dryer having an inlet temperature in the range of 350°C to 450°C and an outlet temperature in the range of 150°C to 200°C.

[0039] According to the implementation scheme of this disclosure, the fifth predetermined temperature is in the range of 500°C to 700°C, and the fifth predetermined time period is in the range of 1 hour to 5 hours.

[0040] According to the embodiments of this disclosure, the predetermined heating rate is in the range of 1°C / min to 5°C / min.

[0041] This disclosure also provides a wear-resistant, high-pore-volume silica-alumina material, characterized by having an wear index of less than 10%; a pore volume greater than 0.7 cc / g; and a pore volume of more than 100 m... 2 / g to 400 m 2 Specific surface area within the range of / g. Attached Figure Description

[0042] This disclosure will now be described with reference to the accompanying drawings, in which: Appendix Figure 1 A flowchart illustrating the method for preparing high-pore-volume silica-alumina materials by spray drying according to this disclosure is provided. Appendix Figure 2 A flowchart illustrating a method for preparing a high-porosity silica-alumina precursor by hydrothermal treatment according to this disclosure is provided. Detailed Implementation

[0043] This disclosure relates to a method for preparing wear-resistant, high-porosity silica-alumina materials.

[0044] The embodiments of this disclosure will now be described with reference to the accompanying drawings.

[0045] The embodiments provided are intended to thoroughly and fully communicate the scope of this disclosure to those skilled in the art. Numerous details regarding specific components and methods are set forth to provide a complete understanding of the embodiments of this disclosure. It will be apparent to those skilled in the art that the details provided in the embodiments should not be construed as limiting the scope of this disclosure. In some embodiments, well-known processes, well-known apparatus structures, and well-known techniques are not described in detail.

[0046] The terminology used in this disclosure is for the purpose of explaining particular embodiments only, and such terminology should not be construed as limiting the scope of this disclosure. As used in this disclosure, the forms “a,” “an,” and “the” may also be intended to include plural forms unless the context clearly indicates otherwise. The terms “comprising,” “containing,” “including,” and “having” are open-ended transitional phrases that specify the presence of the stated features, integers, steps, operations, elements, modules, units, and / or components, but do not preclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof. The specific order of steps disclosed in the methods and processes of this disclosure should not be construed as necessarily requiring them to be performed in the manner described or illustrated. It should also be understood that additional or alternative steps may be employed.

[0047] As used herein, the term “and / or” includes any and all combinations of one or more of the related listed elements.

[0048] The terms first, second, third, etc., should not be construed as limiting the scope of this disclosure, as the aforementioned terms may only be used to distinguish one element, component, region, layer, or portion from another. Terms such as first, second, third, etc., as used herein do not imply a particular order or sequence unless expressly suggested by this disclosure.

[0049] Silica-alumina (SAM) materials are used as carriers and catalysts in the oil refining and chemical industries. The ideal high pore volume, large surface area, and pore size are key characteristics of SAM materials.

[0050] The manufacture of silica-alumina materials is a known process, utilizing expensive organoaluminum and silica sources as their metal alkoxides. However, the synthesis is complicated by the presence of sodium and the high cost of the organoaluminum and silica sources. Furthermore, removing the salts present in the silica-alumina mixture is a challenging process.

[0051] The wear index, particle size, and bulk density of silica-alumina materials are important characteristics for their application in fluidized bed catalytic processes for coal and biomass gasification. Therefore, the preparation of silica-alumina materials with the aforementioned properties for various industrial catalytic applications is desirable.

[0052] This disclosure relates to a method for preparing wear-resistant, high-porosity silica-alumina materials.

[0053] The method for preparing wear-resistant, high-porosity silica-alumina materials includes the following steps: In the first step, a high-pore-volume silica-alumina precursor is prepared by acidifying colloidal silica particles with an acid to obtain acidified silica with a predetermined pH.

[0054] In one exemplary embodiment of this disclosure, the colloidal silica is sodium-free silica. The particle size of the colloidal silica is in the range of 10 nm to 20 nm.

[0055] Colloidal silica is a dispersed phase of silica nanoparticles in an ammonia solution with a pH range of 8 to 10, and the silica particles exist in the form of polymer chains. Upon acidification, it transforms into monomeric reactive silica particles. Larger particle sizes can affect the reactivity of the acidified silica and the surface properties of the final product. Sodium-free silica makes this process feasible and minimizes the tedious washing required to remove sodium ions from the highly viscous gel material used with sodium-containing silica. The presence of sodium ions is known to poison acidic sites in silica-alumina materials, thus affecting catalytic activity. It can be noted that when sodium silicate is used as the silica source, the pore volume of the silica-alumina material is smaller than that when sodium-free silica is used, under similar reaction conditions.

[0056] According to embodiments of this disclosure, the colloidal silica has a silica content ranging from 10% to 40%. In another embodiment of this disclosure, the colloidal silica has a silica content ranging from 25% to 35%. In one exemplary embodiment, the colloidal silica has a silica content of 30%. The colloidal silica is stabilized by using an aqueous ammonia solution.

[0057] According to embodiments of this disclosure, the acid is at least one selected from nitric acid, sulfuric acid, formic acid, and acetic acid. In one exemplary embodiment, the acid is nitric acid. In another exemplary embodiment, the acid is sulfuric acid.

[0058] According to embodiments of this disclosure, the acid is a concentrated acid having a concentration of 65% or higher. In one exemplary embodiment, the acid has a concentration of 65%. In another exemplary embodiment, the acid has a concentration of 95%.

[0059] According to embodiments of this disclosure, the predetermined pH of the acidified silica is in the range of 2.5 to 4. In one exemplary embodiment, the predetermined pH of the acidified silica is 3.5.

[0060] Alternatively, an aluminum precursor solution is prepared by dissolving the aluminum precursor in water at a temperature ranging from 20°C to 40°C. In one exemplary embodiment, the temperature for preparing the aluminum precursor solution is 25°C.

[0061] According to embodiments of this disclosure, the aluminum precursor is at least one selected from aluminum nitrate, aluminum sulfate, aluminum acetate, aluminum formate, aluminum chloride, aluminum oxide, aluminum hydroxide, and aluminum trioxide. In one exemplary embodiment, the aluminum precursor is aluminum nitrate. In another exemplary embodiment, the aluminum precursor is aluminum sulfate.

[0062] According to embodiments of this disclosure, the aluminum precursor is present in an amount ranging from 20% to 50% by mass relative to the total amount of the aluminum precursor solution. In one embodiment, the aluminum precursor is present in an amount of 30% by mass relative to the total amount of the aluminum precursor solution. In an exemplary embodiment, the aluminum precursor is present in an amount of 43% by mass relative to the total amount of the aluminum precursor solution. In this embodiment, water is present in an amount ranging from 50% to 80% by mass relative to the total amount of the aluminum precursor solution.

[0063] The obtained aluminum precursor solution was added to acidified silica under stirring to obtain a silica-alumina sol. The silica-alumina sol thus obtained has a very low pH, i.e., in the range of 2 to 4, and is inherently highly acidic, containing reactive monomeric silica species and dissolved hydrated aluminum precursor.

[0064] The silica / alkali ratio in the silica-alumina precursor was altered by adding aluminum precursor solution and acidified silica in stoichiometric amounts (SiO2:Al2O3: 95:5, 80:20, 70:30, 60:40, 40:60, 30:70, 20:80, 5:95).

[0065] Adding at least one alkali to a silica-alumina sol to bring the pH to a range of 7 to 8 yields a gel. The gel thus obtained is a silica-alumina precipitate formed through an acid-base reaction. In the absence of an alkali, no gel will form from the silica-alumina sol. Therefore, adding an alkali to the silica-alumina sol to bring the pH to a range of 7 to 8 yields a gel.

[0066] According to the implementation scheme, a nonionic surfactant is added to the gel prior to hydrothermal heating. In one exemplary embodiment, the nonionic surfactant is 1 wt% pluronic P123. Adding the nonionic surfactant to the gel prior to hydrothermal heating improves the total pore volume and pore size of the silica-alumina precursor.

[0067] According to embodiments of this disclosure, the base is selected from aqueous ammonia solution and organic amines. In one exemplary embodiment, the base is a 25% aqueous ammonia solution.

[0068] The gel thus obtained is hydrothermally heated in an autoclave at a first predetermined temperature for a first predetermined time period to obtain a heated gel. In this disclosure, the hydrothermal temperature may also be referred to as the aging temperature.

[0069] According to embodiments of this disclosure, the first predetermined temperature is in the range of 150°C to 200°C. In another exemplary embodiment, the first predetermined temperature is 175°C. As illustrated in Examples 1 to 3, temperatures below 150°C require relatively more time. Temperatures above 200°C will not provide the desired properties of the catalyst.

[0070] According to embodiments of this disclosure, the first predetermined time period is in the range of 20 to 30 hours. In one exemplary embodiment, the first predetermined time period is 24 hours.

[0071] The heated gel was cooled to a temperature in the range of 25°C to 40°C, then filtered to obtain a solid, and the solid was washed with an ammonia solution in the range of pH 7 to 9 to obtain a wet filter cake of high-pore-volume silica-alumina precursor.

[0072] Optionally, the wet filter cake is dried at a second predetermined temperature for a second predetermined time period, and then calcined at a third predetermined temperature for a third predetermined time period to obtain a high-pore-volume silica-alumina precursor.

[0073] According to embodiments of this disclosure, the second predetermined temperature is in the range of 100°C to 150°C. In one exemplary embodiment, the second predetermined temperature is 120°C.

[0074] According to embodiments of this disclosure, the second predetermined time period is in the range of 6 hours to 24 hours. In one exemplary embodiment, the second predetermined time period is 12 hours.

[0075] According to embodiments of this disclosure, the third predetermined temperature is in the range of 500°C to 700°C. In one exemplary embodiment, the third predetermined temperature is 600°C.

[0076] According to embodiments of this disclosure, the third predetermined time period is in the range of 1 to 5 hours. In one exemplary embodiment, the third predetermined time period is 3 hours.

[0077] Perform filtration and washing steps on the silica-alumina precursor solids to remove sulfates and / or nitrates from the ammonium precursor and to remove excess ammonia.

[0078] In the second step, at a temperature ranging from 25°C to 40°C, the wet filter cake of the high-porosity silica-alumina precursor or the high-porosity (HVP) silica-alumina precursor is mixed with at least one binder, at least one stabilizer and water to obtain a slurry.

[0079] According to embodiments of this disclosure, the adhesive is selected from reactive colloidal silica and pseudoboehmite alumina. In one exemplary embodiment, the adhesive is reactive colloidal silica.

[0080] According to embodiments of this disclosure, the stabilizer is selected from urea, ammonium carbonate, ammonium bicarbonate, sodium hexametaphosphate, surfactants, polycarboxylic acid ethers, citric acid, oxalic acid, ammonium salts of polyacrylic acid, polydiallyldimethylammonium chloride, hexamethylenetetramine (HMTA), ethylenediaminetetraacetic acid (EDTA), polyacrylamide, and derivatives thereof. In one exemplary embodiment, the stabilizer is urea. In another embodiment of this disclosure, the surfactant is selected from octylphenol ethylene oxide condensate, hexadecyltrimethylammonium bromide, a block copolymer of polyethylene glycol and polypropylene glycol (pluronic P123 block copolymer), and octylphenol ethoxylate. In one exemplary embodiment, the surfactant is octylphenol ethylene oxide condensate (Triton X-100).

[0081] According to embodiments of this disclosure, the binder is present in an amount ranging from 5% to 45% by mass relative to the total amount of the slurry; and the stabilizer is present in an amount ranging from 0.5% to 5% by mass relative to the total amount of the slurry. In one exemplary embodiment, the binder is present in an amount of 30% by mass relative to the total amount of the slurry; and the stabilizer is present in an amount of 1% by mass relative to the total amount of the slurry.

[0082] According to embodiments of this disclosure, the slurry has a solids content in the range of 10% to 30% by mass; and the slurry has a water content in the range of 70% to 90% by mass. In one exemplary embodiment, the slurry has a solids content of 13%.

[0083] In the third step, the slurry is spray-dried at a fourth predetermined temperature for a fourth predetermined time period to obtain spray-dried material in the form of microspheres.

[0084] According to embodiments of this disclosure, the fourth predetermined temperature of the spray dryer is in the range of 150°C to 450°C. In one exemplary embodiment, the fourth predetermined temperature is 180°C. In another exemplary embodiment, the fourth predetermined temperature is 400°C. According to embodiments of this disclosure, spray drying is performed using a spray dryer having an inlet temperature in the range of 350°C to 450°C and an outlet temperature in the range of 150°C to 200°C. In one exemplary embodiment, the spray dryer has an inlet temperature of 400°C and an outlet temperature of 180°C.

[0085] According to embodiments of this disclosure, the fourth predetermined time period ranges from 15 minutes to 60 minutes. In one exemplary embodiment, the fourth predetermined time period is 25 minutes.

[0086] Stabilizers help stabilize the slurry, which contributes to obtaining spray-dried materials with uniform shape and high strength.

[0087] In the final step, the spray-dried material is calcined at a fifth predetermined temperature at a predetermined heating rate for a fifth predetermined time period to obtain a wear-resistant, high-porosity silica-alumina material.

[0088] According to embodiments of this disclosure, the fifth predetermined temperature is in the range of 500°C to 700°C. In one exemplary embodiment, the fifth predetermined temperature is 600°C.

[0089] According to embodiments of this disclosure, the fifth predetermined time period is in the range of 1 to 5 hours. In one exemplary embodiment, the fifth predetermined time period is 3 hours.

[0090] According to embodiments of this disclosure, the predetermined heating rate is in the range of 1°C / min to 5°C / min. In one exemplary embodiment, the predetermined heating rate is 2°C / min.

[0091] According to embodiments of this disclosure, the wear-resistant, high-porosity silica-alumina material is characterized by having an wear index of less than 10%, a pore volume greater than 0.7 cc / g, and a pore volume between 100 and 400 μm. 2 The specific surface area is within the range of / g. In one exemplary embodiment, the wear-resistant, high-porosity silica-alumina material has an abrasion index of 9 and a pore volume of 0.74 cc / g. In another exemplary embodiment, the wear-resistant, high-porosity silica-alumina material has an abrasion index of 7 and a pore volume of 0.70 cc / g.

[0092] Conventional processes require two spray drying steps, one before hydrothermal heating and the other after the addition of binders and stabilizers to the alumina-silica precursor. The method disclosed herein eliminates the need for either a drying or spray drying step prior to hydrothermal heating.

[0093] This disclosure provides a method for preparing wear-resistant, high-porosity silica-alumina materials. For the application of silica-alumina materials in fluidized bed catalytic processes for coal and biomass gasification, the properties of the silica-alumina materials, such as wear index, particle size, and bulk density, are important. Furthermore, this wear-resistant, high-porosity silica-alumina material can be used as a catalyst and adsorbent material in various industrial catalytic processes, such as for catalytic gasification / co-gasification of biomass, petroleum coke, and coal; as a bottom cracking additive / catalyst component in fluid catalytic cracking processes; as a support material / adsorbent for CO2 capture processes; as a metal-impregnated support material for hydrocracking, hydrotreatment, hydroisomerization, hydrogenation, and dehydrogenation; and for catalytic pyrolysis processes. The method of this disclosure uses cost-effective and environmentally friendly conventional raw materials. The method of this disclosure does not utilize any organic source of silica and / or alumina.

[0094] The foregoing description of the embodiments is provided for illustrative purposes and is not intended to limit the scope of this disclosure. Components of a particular embodiment are generally not limited to that particular embodiment and are interchangeable. Such variations should not be considered a departure from this disclosure, and all such modifications are considered to be within the scope of this disclosure.

[0095] The disclosure is further described in conjunction with the following experiments, which are listed for illustrative purposes only and should not be construed as limiting the scope of the disclosure. These experiments can be scaled up to industrial / commercial scale, and the results obtained can be extrapolated to industrial scale.

[0096] Experiment Details

[0097] Example 1: Method for preparing high-porosity silica-alumina precursor

[0098] Concentrated nitric acid (65% or higher) was added dropwise to 267 g of sodium-free colloidal silica (30% silica, pH 9.3) to form acidified silica with a desired pH of 3.5. Separately, 150.1 g of aluminum nitrate was added to 200 ml of demineralized water at 25°C to form an aqueous aluminum nitrate solution (~3.5 M). The aluminum nitrate solution was thoroughly mixed to minimize the formation of any unwanted gels or particles. The resulting aqueous aluminum nitrate solution was mixed with the acidified silica under stirring to obtain a silica-alumina sol. Then, 95 to 100 ml of ammonia solution (25%) was added to the silica-alumina sol to obtain a gel with a pH of 7 to 8. The gel had a solids content of approximately 13 to 14%. This gel was transferred to a 100 ml capacity Teflon-lined stainless steel autoclave and hydrothermally heated at 60°C for 72 hours to obtain a heated gel. The autoclave containing the heated gel was cooled to room temperature (27°C), and the gel was filtered and washed with dilute ammonia (pH 7-9) to remove soluble residual salts and obtain a wet filter cake. The wet filter cake was dried at 120°C for 12 hours and calcined at 600°C for 3 hours to obtain a high-porosity silica-alumina precursor with a silica / alumina ratio of 80:20 (for information on the preparation of high-porosity silica-alumina precursors by hydrothermal treatment, see...). Figure 2 ).

[0099] As shown in Table 1, the calcined material exhibits a thickness of 263 m. 2 The specific surface area is 0.62 cc / g, the pore volume is 0.62 cc / g, and the average pore diameter is 94 Å.

[0100] Example 2: Method for preparing high-porosity silica-alumina precursor

[0101] Concentrated nitric acid (65% or higher) was added dropwise to 267 g of sodium-free colloidal silica (30% silica, pH 9.3) to form acidified silica with the desired pH of 3.5. Separately, 150.1 g of aluminum nitrate was added to 200 ml of demineralized water at 25°C to form an aqueous aluminum nitrate solution. The resulting aqueous aluminum nitrate solution was mixed with the acidified silica under stirring to obtain a silica-alumina sol. Then, 95 to 100 ml of ammonia solution (25%) was added to the silica-alumina sol to obtain a gel with a pH of 7 to 8. The gel had a solids content of approximately 13 to 14%. The gel was transferred to a 100 ml Teflon-lined stainless steel autoclave and hydrothermally heated at 120°C for 24 hours to obtain a heated gel. The autoclave containing the heated gel was cooled to room temperature (27°C), and the gel was filtered and washed with dilute ammonia (pH 7-9) to remove soluble residual salts and obtain a wet filter cake. The wet filter cake was dried at 120°C for 12 hours and calcined at 600°C for 3 hours to obtain a high-pore-volume silica-alumina precursor with a silica / alumina ratio of 80:20.

[0102] As shown in Table 1, the calcined material exhibits a temperature of 265℃ m. 2 The specific surface area is 0.67 cc / g, the pore volume is 0.67 cc / g, and the average pore diameter is 101 Å.

[0103] Example 3: Method for preparing high-porosity silica-alumina precursor

[0104] Concentrated nitric acid (65% or higher) was added dropwise to 267 g of sodium-free colloidal silica (30% silica, pH 9.3) to form acidified silica with a desired pH of 3.5. Separately, 150.1 g of aluminum nitrate was added to 200 ml of demineralized water at 25°C to form an aqueous aluminum nitrate solution. The resulting aqueous aluminum nitrate solution was mixed with the acidified silica under stirring to obtain a silica-alumina sol. Then, 95 to 100 ml of ammonia solution (25%) was added to the silica-alumina sol to obtain a gel with a pH of 7 to 8. The gel had a solids content of approximately 13% to 14%. The gel was transferred to a 100 ml Teflon-lined stainless steel autoclave and hydrothermally heated at 120°C for 72 hours to obtain a heated gel. The autoclave containing the heated gel was cooled to room temperature (27°C), and the gel was filtered and washed with dilute ammonia (pH 7 to 9) to remove soluble residual salts to obtain a wet filter cake. The wet filter cake was dried at 120°C for 12 hours and calcined at 600°C for 3 hours to obtain a high-pore-volume silica-alumina precursor with a silica / alumina ratio of 80:20.

[0105] As shown in Table 1, the calcined material exhibits a thickness of 271 m. 2 The specific surface area is 0.66 cc / g, the pore volume is 0.66 cc / g, and the pore size is 97 Å.

[0106] Example 4: Method for preparing high-porosity silica-alumina precursor according to the present disclosure

[0107] Concentrated nitric acid (65% or higher) was added dropwise to 267 g of sodium-free colloidal silica (30% silica, pH 9.3) to form acidified silica with the desired pH of 3.5. Separately, 150.1 g of aluminum nitrate was added to 200 ml of demineralized water at 25°C to form an aqueous aluminum nitrate solution. The resulting aqueous aluminum nitrate solution was mixed with the acidified silica under stirring to obtain a silica-alumina sol. Then, 95 to 100 ml of ammonia solution (25%) was added to the silica-alumina sol to obtain a gel with a pH of 7 to 8. The gel had a solids content of approximately 13% to 14%. The gel was transferred to a 100 ml Teflon-lined stainless steel autoclave and hydrothermally heated at 175°C for 24 hours to obtain a heated gel. The autoclave containing the heated gel was cooled to room temperature (27°C), and the gel was filtered and washed with dilute ammonia (pH 7-9) to remove soluble residual salts to obtain a wet filter cake. The wet filter cake was dried at 120°C for 12 hours and calcined at 600°C for 3 hours to obtain a high-pore-volume silica-alumina precursor with a silica / alumina ratio of 80:20.

[0108] As shown in Table 1, the calcined material exhibits a thickness of 237 m. 2 The specific surface area is 1.22 cc / g, the pore volume is 1.22 cc / g, and the average pore diameter is 207 Å.

[0109] Example 5: Method for preparing high-porosity silica-alumina precursor according to the present disclosure

[0110] Concentrated sulfuric acid (≥95%) was added dropwise to 267 g of colloidal silica (30% silica, pH 9.3) to form acidified silica with a desired pH of 3.5. Separately, 126.1 g of aluminum sulfate was added to 200 ml of demineralized water at 25°C to form an aqueous aluminum sulfate solution. The resulting aqueous aluminum sulfate solution was mixed with the acidified silica under stirring to obtain ~596 g of silica-alumina sol. Then, 85 to 90 ml of ammonia solution (25%) was added to the silica-alumina sol to obtain a gel with a pH of 7 to 8. The gel had a solids content of approximately 14 to 15%. The silica-alumina gel was hydrothermally heated at 175°C for 24 hours to obtain a heated gel. The heated gel was cooled to room temperature (27°C) and filtered, then washed with dilute ammonia (pH 7 to 9) to remove soluble residual salts to obtain a wet filter cake. The wet filter cake was dried at 120°C for 12 hours and calcined at 600°C for 3 hours to obtain a high-pore-volume silica-alumina precursor with a silica / alumina ratio of 80:20.

[0111] As shown in Table 1, the calcined material exhibits a thickness of 199 m. 2 The specific surface area is 1.08 cc / g, the pore volume is 1.08 cc / g, and the pore size is 218 Å.

[0112] Example 6: A method for preparing high-porosity silica-alumina precursors using sodium silicate (comparative example)

[0113] 126.1 g of aluminum sulfate was dissolved in 200 ml of demineralized water to obtain an aqueous aluminum sulfate solution. 140 ml of 6N H2SO4 was prepared by adding 23 ml of concentrated H2SO4 (≥95%) to 117 ml of demineralized water. A sodium silicate solution (10% silica) was prepared by adding 271 g of liquid sodium silicate solution to demineralized water to prepare an 800 ml solution.

[0114] 200 ml of aluminum sulfate aqueous solution and 140 ml of 6N H2SO4 were mixed together in a container. Then, 800 ml of sodium silicate solution was slowly added to the container. The final pH of the mixture was 3.2. The mixture was aged at room temperature (27°C) for 4 hours. Then, the pH of the slurry was adjusted to 6.5 by adding 75 ml of 25% NH3 aqueous solution. The slurry was hydrothermally heated in an autoclave at 175°C for 24 hours. After aging, the slurry was filtered and washed 8 times with dilute ammonia (pH, 7 to 9) to remove sodium ion impurities and soluble salts to obtain a wet filter cake. The silica-alumina wet filter cake contained 12% solids. The wet filter cake was dried at 120°C for 12 hours and calcined at 600°C for 3 hours to obtain a high-porosity silica-alumina precursor with a silica / alumina ratio of 80:20.

[0115] As shown in Table 1, the calcined material exhibits 81 m 2 The specific surface area is 0.34 cc / g, the pore volume is 0.34 cc / g, and the pore size is 170 Å.

[0116] Table 1. Hydrothermal synthesis of high-porosity silica-alumina precursors: Effects of hydrothermal synthesis temperature (aging temperature), precursor source, and aging time. The surface area, pore volume, and pore size of the silica-alumina material were determined by the N2 adsorption-desorption BET method; $First predetermined temperature; #First predetermined time period; ##Comparative example Table 1 shows the silica-alumina precursors synthesized using aluminum nitrate, aluminum sulfate, and colloidal silica as raw material sources at temperatures of 60°C, 120°C, and 175°C, and over time periods of 24 to 72 hours. Examples 4 and 5 demonstrate that 175°C is the optimal hydrothermal temperature for obtaining high-pore-volume silica-alumina precursors using sodium-free silica and aluminum precursors.

[0117] Example 7: Method for preparing high-porosity silica-alumina precursor according to the present disclosure

[0118] Concentrated nitric acid (65% or higher) was added dropwise to 267 g of silica-free silica (30% silica, pH 9.3) to form acidified silica with the desired pH of 3.5. Separately, 150.1 g of aluminum nitrate was added to 200 ml of demineralized water to form an aqueous aluminum nitrate solution. The resulting aqueous aluminum nitrate solution was mixed with the acidified silica under stirring to obtain a silica-alumina sol. Then, 95 to 100 ml of ammonia solution (25%) was added to the silica-alumina sol to obtain a gel with a pH of 7 to 8. The gel had a solids content of approximately 13 to 14%. The gel was transferred to a 100 ml Teflon-lined stainless steel autoclave and hydrothermally heated at 175°C for 24 hours to obtain a heated gel. The autoclave containing the heated gel was cooled to room temperature (27°C), and the gel was filtered and washed with dilute ammonia (pH 7 to 9) to remove soluble residual salts to obtain a wet filter cake. The wet filter cake was dried at 120°C for 12 hours and calcined at 600°C for 3 hours to obtain a high-pore-volume silica-alumina precursor with a silica / alumina ratio of 70:30.

[0119] As shown in Table 2, the calcined material exhibits a thickness of 290 m. 2 The specific surface area is 1.05 cc / g, the pore volume is 1.05 cc / g, and the average pore diameter is 160 Å.

[0120] Example 8: Method for preparing high-porosity silica-alumina precursor according to the present disclosure

[0121] Concentrated nitric acid (65% or higher) was added dropwise to 267 g of silica-free silica gel (30% silica, pH 9.3) to form acidified silica with the desired pH of 3.5. Separately, aluminum nitrate (150.1 g) was added to 200 ml of demineralized water to form an aqueous aluminum nitrate solution. The resulting aqueous aluminum nitrate solution was mixed with the acidified silica under stirring to obtain a silica-alumina sol. Then, 95 to 100 ml of ammonia solution (25%) was added to the silica-alumina sol to obtain a gel with a pH of 7 to 8. The gel had a solids content of approximately 13 to 14%. The gel was transferred to a 100 ml Teflon-lined stainless steel autoclave and hydrothermally heated at 175°C for 24 hours to obtain a heated gel. The autoclave was cooled to room temperature (27°C), and the gel was filtered and washed with dilute ammonia (pH 7 to 9) to remove soluble residual salts to obtain a wet filter cake. The wet filter cake was dried at 120°C for 12 hours and calcined at 600°C for 3 hours to obtain a high-pore-volume silica-alumina precursor with a silica / alumina ratio of 60:40.

[0122] As shown in Table 2, the calcined material exhibits a thickness of 310 m.2 The specific surface area is 0.97 cc / g, the pore volume is 0.97 cc / g, and the average pore diameter is 125 Å.

[0123] Example 9: Method for preparing high-porosity silica-alumina precursor according to the present disclosure

[0124] Concentrated nitric acid (65% or higher) was added dropwise to 267 g of sodium-free colloidal silica (30% silica, pH 9.3) to form acidified silica with the desired pH of 3.5. Separately, aluminum nitrate (150.1 g) was added to 200 ml of demineralized water at 25°C to form an aqueous aluminum nitrate solution. The resulting aqueous aluminum nitrate solution was mixed with the acidified silica under stirring to obtain a silica-alumina sol. Then, 95 to 100 ml of ammonia solution (25%) was added to the silica-alumina sol to obtain a gel with a pH of 7 to 8. The gel had a solids content of approximately 13% to 14%. The gel was transferred to a 100 ml capacity Teflon-lined stainless steel autoclave and hydrothermally heated at 175°C for 24 hours to obtain a heated gel. The autoclave was cooled to room temperature (27°C), and the gel was filtered and washed with dilute ammonia (pH 7 to 9) to remove soluble residual salts to obtain a wet filter cake. The wet filter cake was dried at 120°C for 12 hours and calcined at 600°C for 3 hours to obtain a high-pore-volume silica-alumina precursor with a silica / alumina ratio of 30:70.

[0125] As shown in Table 2, the calcined material exhibits a thickness of 389 m. 2 The specific surface area is 1.04 cc / g, the pore volume is 1.04 cc / g, and the average pore diameter is 107 Å.

[0126] Example 10: Method for preparing high-porosity silica-alumina precursor according to the present disclosure

[0127] Concentrated nitric acid (65% or higher) was added dropwise to 267 g of colloidal silica (30% silica, pH 9.3) to form acidified silica with a desired pH of 3.5. Separately, 150.1 g of aluminum nitrate was added to 200 ml of demineralized water at 25°C to form an aqueous aluminum nitrate solution. The resulting aqueous aluminum nitrate solution was mixed with the acidified silica under stirring to obtain a silica-alumina sol. Then, 95 to 100 ml of ammonia solution (25%) was added to the silica-alumina sol to bring the final pH to between 7 and 8. 1 wt% of Pluronic P123 nonionic surfactant (molecular weight ~5800 g / mol) was added to the silica-alumina gel. The precipitated gel had a solids content of approximately 13 to 14%. This gel was transferred to a 100 ml capacity Teflon-lined stainless steel autoclave and hydrothermally heated at 175°C for 24 hours to obtain a heated gel. The autoclave was cooled to room temperature (27°C), and the gel was filtered and washed with dilute ammonia (pH 7 to 9) to remove soluble residual salts to obtain a wet filter cake. The wet filter cake was dried at 120°C for 12 hours and calcined at 600°C for 3 hours to obtain a high-pore-volume silica-alumina precursor with a silica / alumina ratio of 30:70.

[0128] As shown in Table 2, the calcined silica-alumina material exhibits a thickness of 295 μm. 2 The specific surface area was 1.35 cc / g, the pore volume was 1.35 cc / g, and the average pore diameter was 184 Å. Adding 1 wt.% P123 increased the pore volume.

[0129] Table 2. Hydrothermal synthesis of high-porosity silica-alumina precursors: Effect of silica / alumina ratio

[0130] #Add 1 wt. % P123; First predetermined temperature; First scheduled time period

[0131] The surface area, pore volume, and average pore size of the silica-alumina precursor were determined by the N2 adsorption-desorption BET method. Table 2 shows that the silica / alumina ratio slightly altered the pore volume. Furthermore, silica-alumina precursors with different silica-alumina ratios and high pore volumes can be prepared.

[0132] Example 11: Method for preparing wear-resistant, high-porosity silica-alumina materials (comparative example)

[0133] A 2 kg batch of silica-alumina precursor (on a dry basis) was prepared by spray drying of a high-porosity silica-alumina slurry. The slurry of the high-porosity (HPV) silica-alumina precursor with a silica / alumina ratio of 80 / 20 from Examples 4 and / or 5 was used. 1.3 kg of reactive colloidal silica (30 wt%) and / or alumina was used as a binder. The slurry was spray-dried for 25 minutes at an inlet air temperature of 400°C and an outlet air temperature of approximately 180°C to obtain microspheres. The microspheres of the spray-dried material were calcined at 600°C at a heating rate of 2°C / min for 3 hours to obtain abrasion-resistant high-porosity silica-alumina material. The properties of the calcined silica-alumina material are given in Table 3 (for the method of preparing high-porosity silica-alumina material by spray drying, see...). Figure 1 ).

[0134] Example 12: Method for preparing wear-resistant, high-porosity silica-alumina material according to the present disclosure

[0135] A 2 kg batch of HPV silica-alumina slurry (on a dry basis) was prepared. This slurry contained 40 wt% silica and 60 wt% alumina. The high-porosity silica-alumina precursor was taken from Example 9. The slurry contained ground silica-alumina precursor powder with an average particle size of less than 5 μm, 1.3 kg of reactive colloidal silica (30 wt%) as a binder, and 20 g of urea as a stabilizer. The final HPV silica-alumina slurry was spray-dried over 25 minutes at an inlet air temperature of 400°C and an outlet air temperature of ~180°C. The spray-dried material was calcined at 600°C for 3 hours at a heating rate of 2°C / min to obtain wear-resistant high-porosity silica-alumina microspheres. The properties of the calcined silica-alumina material are given in Table 3.

[0136] Example 13: Method for preparing wear-resistant, high-porosity silica-alumina material according to the present disclosure

[0137] A 2 kg batch of HPV silica-alumina slurry (dry basis) containing 40 wt% silica and 60 wt% alumina was prepared. This high-porosity silica-alumina precursor was obtained from a mixture of Examples 8, 9, and 10. The slurry contained milled silica-alumina precursor powder with an average particle size of less than 5 μm, 1.3 kg of reactive colloidal silica (30 wt%) as a binder, and 20 g of Triton X-100 as a slurry stabilizer. The final slurry was spray-dried over 25 minutes at an inlet air temperature of 400°C and an outlet air temperature of approximately 180°C. The spray-dried material was calcined at 600°C for 3 hours at a heating rate of 2°C / min to obtain wear-resistant high-porosity silica-alumina microspheres. The properties of the calcined silica-alumina material are given in Table 3.

[0138] Table 3. Physicochemical properties of silica-alumina materials after spray drying and calcination Total pore volume was determined by the N2 adsorption-desorption BET method; Comparative example (without stabilizer). Spray-dried silica-alumina materials showed improvement at 100 μm. 2 / g to 400 m 2 Specific surface area values ​​within the range of / g.

[0139] The spray-dried high-porosity silica-alumina material is not limited to the silica-alumina composition described in Table 3, but can be prepared from 5 wt% to 95 wt% silica using high-porosity silica and alumina precursors, reactive binders and slurry stabilizers, and the amount of alumina can be balanced, and vice versa.

[0140] Using stabilizers such as urea and Triton X-100 to improve the wear index value to <10, as shown in Examples 12 and 13, is desirable.

[0141] Technological progress

[0142] The present disclosure described above has several technical advantages, including but not limited to a method for preparing wear-resistant, high-porosity silica-alumina materials, wherein the method: Simple, cost-effective, and efficient; Used in fluid catalytic processes; Provide high-pore-volume silica-alumina precursors; and Provide wear-resistant, high-pore-volume silica-alumina materials; Throughout this specification, the word “comprise” or variations such as “comprises” or “comprising” shall be understood to mean including the said element, integer or step, or group of elements, integers or steps, but not excluding any other element, integer or step, or group of elements, integers or steps.

[0143] The use of the expressions “at least” or “at least one” indicates the use of one or more elements or components or amounts, as may be used in embodiments of this disclosure, to achieve one or more desired purposes or results.

[0144] Any discussion of documents, actions, materials, devices, articles, or similar content contained in this specification is for the purpose of providing background to this disclosure only. It should not be construed as an admission that any or all of these matters constitute part of the prior art or common general knowledge existing anywhere in the relevant field of this disclosure prior to the priority date of this application.

[0145] The values ​​mentioned for various physical parameters, dimensions or quantities are approximate only, and values ​​higher or lower than the values ​​assigned to parameters, dimensions or quantities are assumed to fall within the scope of this disclosure unless specifically stated otherwise in the specification.

[0146] While this document focuses on the components and elements of the preferred embodiments, it should be understood that many embodiments can be made, and many changes can be made to the preferred embodiments without departing from the principles of this disclosure. These and other changes to the preferred embodiments, as well as other embodiments of this disclosure, will be apparent to those skilled in the art from the content of this disclosure, and it should be clearly understood that the foregoing descriptive content is to be interpreted as illustrative rather than limiting.

Claims

1. A method for preparing wear-resistant, high-porosity silica-alumina material, the method comprising the following steps: A) High-porosity silica-alumina precursors were prepared by the following method: (a) Acidifying colloidal silica particles by using an acid to obtain acidified silica with a predetermined pH value; (b) An aluminum precursor solution was prepared separately by dissolving the aluminum precursor in water by stirring at a temperature ranging from 20°C to 40°C. (c) The aluminum precursor solution is added to the acidified silica under stirring to obtain silica-alumina sol; (d) Add at least one base to the silica-alumina sol to bring the pH value to the range of 7 to 8 to obtain a gel; (e) The gel is hydrothermally heated in an autoclave at a first predetermined temperature for a first predetermined time period to obtain a heated gel; (f) Cool the heated gel to a temperature in the range of 25°C to 40°C, then filter it to obtain a solid, and wash the solid with an ammonia solution with a pH in the range of 7 to 9 to obtain a wet filter cake of the high-porosity silica-alumina precursor. (g) Optionally, the wet filter cake is dried at a second predetermined temperature for a second predetermined time period, and then calcined at a third predetermined temperature for a third predetermined time period to obtain the high-porosity silica-alumina precursor; B) At a temperature in the range of 25°C to 40°C, at least one binder, at least one stabilizer and water are mixed into the wet filter cake of the high-porosity silica-alumina precursor of step (f) or the high-porosity silica-alumina precursor of step (g) to obtain a slurry. C) The slurry is spray-dried at a fourth predetermined temperature for a fourth predetermined time period to obtain a spray-dried material in the form of microspheres; as well as D) The spray-dried material is calcined at a fifth predetermined temperature at a predetermined heating rate for a fifth predetermined time period to obtain the wear-resistant high-porosity silica-alumina material.

2. The method according to claim 1, wherein the acid is at least one selected from nitric acid, sulfuric acid, formic acid and acetic acid.

3. The method according to claim 1, wherein the acid is a concentrated acid with a concentration of 65% or higher.

4. The method according to claim 1, wherein the predetermined pH value of the acidified silica is in the range of 2.5 to 4.

5. The method according to claim 1, wherein the colloidal silica is sodium-free silica.

6. The method according to claim 1, wherein the particle size of the colloidal silica is in the range of 10 nm to 20 nm.

7. The method according to claim 1, wherein the aluminum precursor is selected from at least one of aluminum nitrate, aluminum sulfate, aluminum acetate, aluminum formate, aluminum chloride, aluminum oxide, aluminum hydroxide and aluminum trihydride.

8. The method of claim 1, wherein a nonionic surfactant is added to the gel prior to hydrothermal heating; wherein the nonionic surfactant is a block copolymer of polyethylene glycol and polypropylene glycol.

9. The method according to claim 1, wherein the base is selected from aqueous ammonia solution and organic amines.

10. The method of claim 1, wherein the first predetermined temperature is in the range of 150°C to 200°C.

11. The method according to claim 1, wherein the first predetermined time period is in the range of 20 to 30 hours.

12. The method of claim 1, wherein the second predetermined temperature is in the range of 100°C to 150°C.

13. The method of claim 1, wherein the second predetermined time period is in the range of 6 hours to 24 hours.

14. The method according to claim 1, wherein the third predetermined temperature is in the range of 500°C to 700°C.

15. The method according to claim 1, wherein the third predetermined time period is in the range of 1 hour to 5 hours.

16. The method of claim 1, wherein the adhesive is selected from reactive colloidal silica and pseudoboehmite alumina.

17. The method according to claim 1, wherein the stabilizer is selected from urea, ammonium carbonate, ammonium bicarbonate, sodium hexametaphosphate, polycarboxylic acid ether, citric acid, oxalic acid, ammonium salts of polyacrylic acid, polydiallyldimethylammonium chloride, hexamethylenetetramine (HMTA), ethylenediaminetetraacetic acid (EDTA), polyacrylamide, and derivatives thereof.

18. The method of claim 17, wherein the surfactant is selected from octylphenol ethylene oxide condensate, hexadecyltrimethylammonium bromide, block copolymers of polyethylene glycol and polypropylene glycol, and octylphenol ethoxylate.

19. The method according to claim 1, wherein the solid content of the slurry is in the range of 10% by mass to 30% by mass, and the moisture content of the slurry is in the range of 70% by mass to 90% by mass.

20. The method according to claim 1, wherein the fourth predetermined temperature is in the range of 150°C to 450°C; and the fourth predetermined time period is in the range of 15 minutes to 60 minutes.

21. The method of claim 20, wherein the spray drying is performed using a spray dryer having an inlet temperature in the range of 350°C to 450°C and an outlet temperature in the range of 150°C to 200°C.

22. The method according to claim 1, wherein the fifth predetermined temperature is in the range of 500°C to 700°C; and the fifth predetermined time period is in the range of 1 hour to 5 hours.

23. The method according to claim 1, wherein the predetermined heating rate is in the range of 1°C / min to 5°C / min.

24. A wear-resistant, high-porosity silica-alumina material, characterized in that... have: a. Wear index less than 10%; b. Pore volume greater than 0.7 cc / g; and c. At 100 m 2 / g to 400 m 2 Specific surface area within the range of / g.